INVESTOR BEHAVIOUR IN FINANCIAL MARKETS: TRENDS, INSIGHTS, AND REGIONAL PERSPECTIVES - Kakkattuchali, Aboobacker Siddeeq; Ayoob C.P; PK, Munavar Jasim; Edathil, Kamalam; Muhammed Faisal. T (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Investor behaviour plays a crucial role in shaping the dynamics of stock market investments, particularly in the context of emerging markets like India. This study examines the investor behaviour in Tirurangadi Municipality, a regional economic hub, by exploring how local investors engage with the stock market. It analyzes the factors driving their decision-making processes and compares these behaviours with global and national trends. Using theoretical frameworks such as Kahneman and Tversky’s (1979) prospect theory, and empirical studies on psychological, cultural, and economic influences, the research investigates behavioural patterns like loss aversion, overconfidence, and herding. The findings highlight the distinct socio-economic and cultural factors affecting investment decisions in the region, reflecting broader insights from emerging markets. Additionally, the study explores the role of financial literacy in improving investor satisfaction and market stability. By providing a comprehensive understanding of investor behaviour in this localized context, the paper aims to inform both policymakers and market participants on the potential strategies to enhance investor confidence and promote a stable financial ecosystem.